Composite semi-flexible pavement early strength grouting material and preparation method and application thereof
By using the formula of composite semi-flexible pavement premature grouting materials in cement-based grouting materials, including cement, quartz sand, fly ash float beads, microsilicon powder, expansion agent, composite premature water reducing agent and retarder, The contradiction between liquidity and early strength in the prior art was solved, and the early strength and fast hardness of grouting materials were achieved, high flow and low dry shrinkage were achieved, and the requirements of rapid open traffic and related standards were met.
Patent Information
- Application Number
- CN202411614713.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There is a contradiction between the liquidity and early strength of the existing cement-based grouting materials, which is difficult to meet the demand for rapid opening of transportation. At the same time, the flexural strength is low and the dry shrinkage rate is large, which cannot meet the technical/performance index requirements of the China Engineering Construction Standardization Association. .
Compound semi-flexible pavement premature grouting materials, including cement, quartz sand, fly ash drift beads, microsilicon powder, expansion agent, composite premature water reducing agent, retarder and water, through sulfur aluminate cement Combination with silicate cement, combined with the grading of quartz sand and the use of expansion agent, improve the fluidity and early strength of the grouting material, and further improve the early strength and late strength through the use of composite early strength reducers .
It realizes the early strength, fast hardness, high flow, high viscosity and low dry shrinkage of grouting materials, and can seamlessly bond with the asphalt mixture matrix, without obvious shrinkage after hardening, significantly shortening the road surface opening time, and meet relevant standards. technical/performance indicators.
Smart Images

Figure BDA0005131859970000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a composite semi-flexible pavement early-strength grouting material and a preparation method and application thereof. Background Art
[0002] With the long-term and sustainable green development of my country's economy, high-quality roads provide an indispensable guarantee for the rapid development of society. Roads are the arteries of economic development. As an important part of road engineering, pavement is of great significance to the comfort and safety of road users, the service life of roads, urban transportation and environmental protection.
[0003] At present, the road pavement in my country is mainly asphalt concrete pavement and cement concrete pavement. Cement concrete road pavement is a rigid pavement with high requirements for roadbed stability, complex joint setting, long construction and maintenance time, poor driving comfort, difficulty in later maintenance, and easy misalignment. Asphalt concrete pavement is easily affected by ambient temperature and vehicle load. When the temperature is high in summer, the viscosity of asphalt decreases, the cohesion between aggregates weakens, and shear deformation damage such as rutting, potholes, and waves is prone to occur after long-term vehicle rolling. When the temperature is low, the viscosity of asphalt increases, resulting in a significant decrease in deformation resistance, and the overall brittleness causes the road surface to crack, produce transverse and longitudinal cracks, further cause surface water to penetrate into the base and even the roadbed, and ultimately cause comprehensive damage to the road.
[0004] Semi-flexible pavement is a new type of composite pavement based on high-porosity asphalt mixture, which is rolled and then added with a large amount of cement-based mortar. It combines the advantages of asphalt pavement, which has good flexibility, excellent crack resistance, and seamless construction, and cement concrete pavement, which has high rigidity, strong bearing capacity, and good rutting resistance. It can reduce noise pollution, improve driving comfort, extend road service life, improve road safety, and reduce environmental burden, which is beneficial to environmental protection and carbon emissions. It is of great significance to urban transportation and environmental protection.
[0005] Cement-based grouting material is an important component of semi-flexible pavement materials, and its working performance and mechanical properties determine the bearing capacity and volume stability of the pavement. There is a certain contradiction between the fluidity and early strength of cement-based grouting materials. For cement-based grouting materials for semi-flexible pavements, in order to meet the purpose of rapid opening of traffic, it is generally required to have a higher early strength, but this will reduce the fluidity of the grouting material, making it difficult to pour during the construction process and increase the difficulty of construction. At present, the grouting materials publicly reported in the prior art CN115947578A, CN116514483A, CN105016678A, CN113277809A, and CN113045278A still have certain problems and / or deficiencies, such as the contradiction between fluidity and early strength, as well as low flexural strength and large shrinkage rate, which cannot meet the technical / performance index requirements of the China Association for Engineering Construction Standardization standard "Technical Specifications for Grouted Semi-Flexible Pavements of Urban Roads" (T / CECS1016-2022). Therefore, there is an urgent need for a composite semi-flexible pavement early-strength grouting material with the advantages of early strength and fast hardening, high fluidity, high viscosity and low shrinkage rate to solve the above problems. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a composite semi-flexible pavement early-strength grouting material and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The invention provides a composite semi-flexible pavement early strength grouting material, comprising the following raw materials in parts by weight: 25-55 parts of cement, 10-30 parts of quartz sand, 9-15 parts of fly ash floating beads, 8-20 parts of microsilica powder, 2-8 parts of expansion agent, 0.16-0.3 parts of composite early strength water reducing agent, 0.05-0.2 parts of retarder and 25-45 parts of water;
[0009] The composite early strength water reducing agent is compounded by an inorganic early strength agent, an organic early strength agent and a water reducing agent;
[0010] The cement is composed of silicate cement and sulphoaluminate cement in a mass ratio of (10-20):(80-90).
[0011] Preferably, the mass ratio of the inorganic early strength agent to the organic early strength agent is (0.1-0.3):(0.12-0.55); the total mass concentration of the inorganic early strength agent and the organic early strength agent in the composite early strength water-reducing agent is 25%.
[0012] Preferably, the inorganic early strength agent includes one or more of calcium nitrate, sodium sulfate and potassium sulfate.
[0013] Preferably, the organic early strength agent includes one or more of triethanolamine, diethanolamine, calcium formate and calcium acetate.
[0014] Preferably, the water reducer includes one of a polycarboxylate water reducer, a naphthalene water reducer, an aminosulfonate, and an aliphatic water reducer.
[0015] Preferably, the particle size of the quartz sand is 40-200 mesh;
[0016] The content of silicon oxide in the fly ash floating beads is ≥50%, the average diameter is 0.16-1.41 μm, and the minimum particle size is 0.09 μm;
[0017] The silicon dioxide content in the microsilica powder is ≥95%, the average diameter is 0.1-0.15 μm, and the minimum particle size is 0.01 μm.
[0018] Preferably, the expansion agent includes one or more of sulphoaluminate expansion agents, calcium oxide expansion agents, and magnesium oxide expansion agents;
[0019] The retarder includes one or more of citric acid, tartaric acid, sodium gluconate, boric acid and white sugar.
[0020] The present invention provides a method for preparing the composite semi-flexible pavement early strength grouting material described in the above technical solution, comprising the following steps:
[0021] (1) Cement, quartz sand, fly ash beads, microsilica powder and expansion agent are uniformly mixed to obtain mixture A;
[0022] (2) compounding an inorganic early strength agent, an organic early strength agent and a water reducer to obtain a composite early strength water reducer, and premixing the obtained composite early strength water reducer with a retarder and water to obtain a liquid phase B;
[0023] (3) adding the liquid phase B obtained in step (2) to the mixture A obtained in step (1) in portions, and obtaining the composite semi-flexible pavement early strength grouting material through forced mixing and stirring;
[0024] There is no order of precedence for steps (1) and (2).
[0025] The present invention also provides the application of the composite semi-flexible pavement early-strength grouting material described in the above technical solution in road engineering.
[0026] Compared with the prior art, the present invention has the following advantages and technical effects:
[0027] (1) The composite semi-flexible pavement early-strength grouting material provided by the present invention is compounded with sulphoaluminate cement and ordinary silicate cement in different proportions, and the grading of quartz sand is adjusted. At the same time, high-quality fly ash beads and high-activity microsilica powder from power plant flotation are added to improve the working fluidity of the grouting material. An expansion agent is then added to compensate for the late shrinkage performance of the grouting material. The composite early-strength water-reducing agent is used to further improve the early strength of the grouting material and shorten the pavement opening time.
[0028] (2) The inorganic early strength agent and the organic early strength agent in the composite early strength water reducing agent of the present invention have a synergistic effect. The early strength agent can improve the electrokinetic potential of the cement paste, promote the reaction of C3A and AF t The formation of early strength agent Ca 2+ Can increase the Ca content in the liquid phase 2+ concentration, improve the hydration rate of sulphoaluminate cement and silicate cement, increase the solid phase ratio, which is beneficial to the formation of cement stone structure and increase the early strength.
[0029] (3) The composite semi-flexible pavement early-strength grouting material of the present invention has the advantages of early strength, rapid hardening and high fluidity, and at the same time has the characteristics of high viscosity and low shrinkage rate. It can be seamlessly bonded to the asphalt mixture matrix, and there is no obvious shrinkage after hardening, and the actual application effect is good. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.
[0032] The embodiment of the present invention provides a composite semi-flexible pavement early strength grouting material, comprising the following raw materials in parts by weight: 25-55 parts of cement, 10-30 parts of quartz sand, 9-15 parts of fly ash beads, 8-20 parts of microsilica powder, 2-8 parts of expansion agent, 0.16-0.3 parts of composite early strength water reducing agent, 0.05-0.2 parts of retarder and 25-45 parts of water;
[0033] The composite early strength water reducing agent is compounded by an inorganic early strength agent, an organic early strength agent and a water reducing agent;
[0034] The cement is composed of silicate cement and sulphoaluminate cement in a mass ratio of (10-20):(80-90).
[0035] The present invention utilizes sulphoaluminate cement and ordinary silicate cement in different proportions, adjusts the gradation of quartz sand, and simultaneously adds high-quality fly ash beads and high-activity microsilica powder from power plant flotation to improve the working fluidity of the grouting material. An expansion agent is added to compensate for the late shrinkage performance of the grouting material, and a composite early-strength water-reducing agent is used to further improve the early strength of the grouting material and shorten the road surface opening time.
[0036] In a preferred embodiment, the composite early strength water reducing agent is compounded by an inorganic early strength agent, an organic early strength agent and a water reducing agent. The present invention compounds various types of early strength agents with water reducing agents to form a composite early strength water reducing agent, which can not only improve the early strength of concrete, but also facilitate the later strength growth, and also has a certain water reducing effect, which is more convenient for construction and use. The organic early strength agent and the inorganic early strength agent in the present invention have a synergistic effect. The early strength agent can improve the electromotive potential of the cement paste, promote the reaction of C3A and AF t The formation of early strength agent Ca 2+ Can increase the Ca content in the liquid phase 2+ concentration, thereby increasing the hydration rate of cement, increasing the solid phase ratio, which is beneficial to the formation of cement stone structure and increasing the early strength.
[0037] In a preferred embodiment, the mass ratio of the inorganic early strength agent to the organic early strength agent is (0.1-0.3):(0.12-0.55); the total mass concentration of the inorganic early strength agent and the organic early strength agent in the composite early strength water reducing agent is 25%.
[0038] In a preferred embodiment, the composite early strength water reducing agent contains Ca 2+ .
[0039] In a preferred embodiment, the inorganic early strength agent includes one or more of calcium nitrate, sodium sulfate, and potassium sulfate, more preferably sodium sulfate.
[0040] In a preferred embodiment, the organic early strength agent includes one or more of triethanolamine, diethanolamine, calcium formate, and calcium acetate, more preferably calcium formate and triethanolamine. In a preferred embodiment, when the organic early strength agent is calcium formate and triethanolamine, the mass ratio of calcium formate to triethanolamine is (0.1-0.3):(0.02-0.25).
[0041] In a preferred embodiment, the water reducer includes one of a polycarboxylate water reducer, a naphthalene-based water reducer, an aminosulfonate, and an aliphatic-based water reducer, and more preferably a polycarboxylate water reducer.
[0042] In a preferred embodiment, the cement is composed of silicate cement and sulphoaluminate cement in a mass ratio of (10-20):(80-90). The present invention utilizes the compounding of sulphoaluminate cement and silicate cement to obtain a composite semi-flexible pavement early strength grouting material that does not shrink in the later stage and is not easily deformed under the action of pavement load.
[0043] In a preferred embodiment, the particle size of the quartz sand is 40-200 mesh; the gradation of the quartz sand is 40-79 mesh: 80-119 mesh: 120-159 mesh: 160-200 mesh = 325:50:50:100.
[0044] In a preferred embodiment, the content of silicon oxide in the fly ash floating beads is ≥50%, the average diameter is 0.16-1.41 μm, and the minimum particle size is 0.09 μm.
[0045] In a preferred embodiment, the silicon dioxide content in the microsilica powder is ≥95%, the average diameter is 0.1-0.15 μm, and the minimum particle size is 0.01 μm.
[0046] In a preferred embodiment, the expansion agent includes one or more of a sulphoaluminate expansion agent, a calcium oxide expansion agent, and a magnesium oxide expansion agent, and is more preferably a sulphoaluminate expansion agent.
[0047] In a preferred embodiment, the retarder includes one or more of citric acid, tartaric acid, sodium gluconate, boric acid, and white sugar, more preferably sodium gluconate and white sugar.
[0048] The present invention provides a method for preparing the composite semi-flexible pavement early strength grouting material described in the above technical solution, comprising the following steps:
[0049] (1) Cement, quartz sand, fly ash beads, microsilica powder and expansion agent are mixed uniformly to obtain mixture A;
[0050] (2) Compounding an inorganic early strength agent, an organic early strength agent and a water reducer to obtain a composite early strength water reducer, and premixing the obtained composite early strength water reducer with a retarder and water to obtain a liquid phase B;
[0051] (3) adding the liquid phase B obtained in step (2) to the mixture A obtained in step (1) in portions, and obtaining the composite semi-flexible pavement early strength grouting material through forced mixing and stirring;
[0052] There is no order of precedence for steps (1) and (2).
[0053] The present invention also provides the application of the composite semi-flexible pavement early-strength grouting material described in the above technical solution in road engineering.
[0054] Unless otherwise specified, parts in the embodiments of the present invention represent “parts by weight”.
[0055] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0056] In the following examples, the particle size of the quartz sand is 40-200 mesh, and the gradation of the quartz sand is 40-79 mesh: 80-119 mesh: 120-159 mesh: 160-200 mesh = 325:50:50:100;
[0057] The silica content in fly ash floating beads is ≥50%, the average diameter is 0.16-1.41μm, and the minimum particle size is 0.09μm;
[0058] The silicon dioxide content in microsilica powder is ≥95%, the average diameter is 0.1-0.15μm, and the minimum particle size is 0.01μm.
[0059] Example 1
[0060] A method for preparing a composite semi-flexible pavement early strength grouting material, the specific steps are as follows:
[0061] (1) 50 parts of sulphoaluminate cement and silicate cement in a mass ratio of 80:20, 30 parts of quartz sand, 15 parts of fly ash beads, 18 parts of microsilica powder, and 8 parts of sulphoaluminate expansion agent were weighed and added into a stirring pot and mixed evenly to obtain a mixture A;
[0062] (2) weighing 0.3 parts of sodium sulfate, 0.3 parts of calcium formate, and 0.05 parts of triethanolamine and adding them to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25 wt%; premixing 0.16 parts of the composite early strength water reducer, 0.02 parts of sodium gluconate, 0.04 parts of white sugar, and 28 parts of water to obtain a liquid phase B;
[0063] (3) adding the liquid phase B obtained in step (2) into a stirring pot twice and forcibly mixing with the mixture A in step (1), stirring for 3 minutes, and obtaining a composite semi-flexible pavement early strength grouting material.
[0064] Example 2
[0065] A method for preparing a composite semi-flexible pavement early strength grouting material, the specific steps are as follows:
[0066] (1) 45 parts of sulphoaluminate cement and silicate cement in a mass ratio of 80:20, 27 parts of quartz sand, 12 parts of fly ash beads, 20 parts of microsilica powder, and 7 parts of sulphoaluminate expansion agent were weighed and added into a stirring pot and mixed evenly to obtain a mixture A;
[0067] (2) weighing 0.2 parts of sodium sulfate, 0.3 parts of calcium formate, and 0.10 parts of triethanolamine and adding them to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25 wt%; premixing 0.18 parts of the composite early strength water reducer, 0.03 parts of sodium gluconate, 0.06 parts of white sugar, and 36 parts of water to obtain a liquid phase B;
[0068] (3) adding the liquid phase B obtained in step (2) into a stirring pot twice and forcibly mixing with the mixture A in step (1), stirring for 3 minutes, and obtaining a composite semi-flexible pavement early strength grouting material.
[0069] Example 3
[0070] A method for preparing a composite semi-flexible pavement early strength grouting material, the specific steps are as follows:
[0071] (1) 40 parts of sulphoaluminate cement and silicate cement in a mass ratio of 80:20, 22.5 parts of quartz sand, 10 parts of fly ash beads, 15 parts of microsilica powder, and 6 parts of sulphoaluminate expansion agent were weighed and added into a stirring pot and mixed evenly to obtain a mixture A;
[0072] (2) weighing 0.1 parts of sodium sulfate, 0.3 parts of calcium formate, and 0.15 parts of triethanolamine and adding them to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25 wt%; premixing 0.20 parts of the composite early strength water reducer, 0.04 parts of sodium gluconate, 0.08 parts of white sugar, and 25 parts of water to obtain a liquid phase B;
[0073] (3) adding the liquid phase B obtained in step (2) into a stirring pot twice and forcibly mixing with the mixture A in step (1), stirring for 3 minutes, and obtaining a composite semi-flexible pavement early strength grouting material.
[0074] Example 4
[0075] A method for preparing a composite semi-flexible pavement early strength grouting material, the specific steps are as follows:
[0076] (1) 35 parts of sulphoaluminate cement and silicate cement in a mass ratio of 80:20, 16 parts of quartz sand, 11 parts of fly ash beads, 19 parts of microsilica powder, and 5 parts of sulphoaluminate expansion agent were weighed and added into a stirring pot and mixed evenly to obtain a mixture A;
[0077] (2) weighing 0.3 parts of sodium sulfate, 0.2 parts of calcium formate, and 0.20 parts of triethanolamine and adding them to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25 wt%; premixing 0.22 parts of the composite early strength water reducer, 0.04 parts of sodium gluconate, 0.04 parts of white sugar, and 25 parts of water to obtain a liquid phase B;
[0078] (3) adding the liquid phase B obtained in step (2) into a stirring pot twice and forcibly mixing with the mixture A in step (1), stirring for 3 minutes, and obtaining a composite semi-flexible pavement early strength grouting material.
[0079] Example 5
[0080] A method for preparing a composite semi-flexible pavement early strength grouting material, the specific steps are as follows:
[0081] (1) 50 parts of sulphoaluminate cement and silicate cement in a mass ratio of 80:20, 26 parts of quartz sand, 9 parts of fly ash beads, 20 parts of microsilica powder, and 6 parts of sulphoaluminate expansion agent were weighed and added into a stirring pot and mixed evenly to obtain a mixture A;
[0082] (2) weighing 0.3 parts of sodium sulfate, 0.3 parts of calcium formate, and 0.15 parts of triethanolamine and adding them to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25 wt%; premixing 0.25 parts of the composite early strength water reducer, 0.02 parts of sodium gluconate, 0.04 parts of white sugar, and 32 parts of water to obtain a liquid phase B;
[0083] (3) adding the liquid phase B obtained in step (2) into a stirring pot twice and forcibly mixing with the mixture A in step (1), stirring for 3 minutes, and obtaining a composite semi-flexible pavement early strength grouting material.
[0084] Example 6
[0085] A method for preparing a composite semi-flexible pavement early strength grouting material, the specific steps are as follows:
[0086] (1) 50 parts of sulphoaluminate cement and silicate cement in a mass ratio of 80:20, 26 parts of quartz sand, 9 parts of fly ash beads, 8 parts of microsilica powder, and 6 parts of sulphoaluminate expansion agent were weighed and added into a stirring pot and mixed evenly to obtain a mixture A;
[0087] (2) weighing 0.3 parts of sodium sulfate, 0.3 parts of calcium formate, and 0.20 parts of triethanolamine and adding them to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25 wt%; premixing 0.20 parts of the composite early strength water reducer, 0.03 parts of sodium gluconate, 0.04 parts of white sugar, and 31 parts of water to obtain a liquid phase B;
[0088] (3) adding the liquid phase B obtained in step (2) into a stirring pot twice and forcibly mixing with the mixture A in step (1), stirring for 3 minutes, and obtaining a composite semi-flexible pavement early strength grouting material.
[0089] Comparative Example 1
[0090] A method for preparing a composite semi-flexible pavement early strength grouting material, the specific steps are as follows:
[0091] (1) Weigh 50 parts of sulphoaluminate cement, 26 parts of quartz sand, 9 parts of fly ash beads, 8 parts of microsilica powder, and 6 parts of sulphoaluminate expansion agent into a stirring pot and mix well to obtain a mixture A;
[0092] (2) weighing 0.3 parts of sodium sulfate, 0.3 parts of calcium formate, and 0.20 parts of triethanolamine and adding them to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25 wt%; premixing 0.20 parts of the composite early strength water reducer, 0.03 parts of sodium gluconate, 0.04 parts of white sugar, and 31 parts of water to obtain a liquid phase B;
[0093] (3) adding the liquid phase B obtained in step (2) into a stirring pot twice and forcibly mixing with the mixture A in step (1), stirring for 3 minutes, and obtaining a composite semi-flexible pavement early strength grouting material.
[0094] Comparative Example 2
[0095] A method for preparing a composite semi-flexible pavement early strength grouting material, the specific steps are as follows:
[0096] (1) 50 parts by weight of silicate cement, 26 parts by weight of quartz sand, 9 parts by weight of fly ash beads, 8 parts by weight of microsilica powder, and 6 parts by weight of sulphoaluminate expansion agent were added into a stirring pot and mixed evenly to obtain a mixture A;
[0097] (2) weighing 0.3 parts of sodium sulfate, 0.3 parts of calcium formate, and 0.20 parts of triethanolamine and adding them to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25 wt%; premixing 0.20 parts of the composite early strength water reducer, 0.03 parts of sodium gluconate, 0.04 parts of white sugar, and 31 parts of water to obtain a liquid phase B;
[0098] (3) adding the liquid phase B obtained in step (2) into a stirring pot twice and forcibly mixing with the mixture A in step (1), stirring for 3 minutes, and obtaining a composite semi-flexible pavement early strength grouting material.
[0099] Comparative Example 3
[0100] Sika Grout 214 cement-based grout is commercially available.
[0101] Comparative Example 4
[0102] The difference from Example 1 is that in step (2), 8 parts of water are added, and the other steps are the same as Example 1.
[0103] Comparative Example 5
[0104] The difference from Example 1 is that in step (1), 50 parts of sulphoaluminate cement and silicate cement are weighed in a mass ratio of 20:80, and the other steps are the same as Example 1.
[0105] Comparative Example 6
[0106] The difference from Example 1 is that in step (2), 0.5 parts of sodium sulfate, 0.1 parts of calcium formate, and 0.05 parts of triethanolamine are weighed and added to the polycarboxylate water reducer to prepare a composite early strength water reducer with a concentration of 25wt%. The other steps are the same as in Example 1.
[0107] The performance of the semi-flexible pavement cement-based grouting materials in Examples 1-6 and Comparative Examples 1-6 was tested with reference to GBT50448-2015 "Technical Specifications for the Application of Cement-Based Grouting Materials" and TCECS1016-2022 "Technical Specifications for Grouting Semi-Flexible Pavements of Urban Roads". The test results are shown in Table 1.
[0108] Table 1 Performance of semi-flexible pavement cement-based grouting materials in Examples 1-6 and Comparative Examples 1-6
[0109]
[0110] As can be seen from Table 1, the composite semi-flexible pavement early strength grouting material provided by the present invention utilizes the compounding of sulphoaluminate cement and silicate cement, and the later strength does not shrink, and it is not easy to deform under the action of the pavement load. At the same time, the initial fluidity time of the 6 groups of embodiments of the present invention is significantly reduced compared with the comparative example. Compared with the commercially available semi-flexible pavement cement-based grouting material, the sulphoaluminate cement and silicate cement in Example 6 of the present invention are compounded according to a mass ratio of 80:20, and the grading of quartz sand is 40-79 mesh: 80-119 mesh: 120-159 mesh: 160-200 mesh = 325:50:50:100. At the same time, 9% of fly ash floating beads and 8% of microsilica powder are added to adjust the fluidity of the grouting material. The initial fluidity of the obtained semi-flexible pavement cement-based grouting material is reduced from 24.5s to 12.5s, and the half-hour fluidity is reduced from 43s to 14.8s, and the loss is significantly reduced. In addition, the present invention uses a composite early strength water reducing agent, which not only ensures the water reduction rate, but also utilizes the synergistic effect of inorganic and organic early strength agents to significantly enhance the early strength of the semi-flexible pavement grouting material. The final 3h compressive strength reaches 24.6MPa, which can significantly shorten the road traffic opening time.
[0111] In addition, although the 3h compressive strength in Comparative Example 6 is higher than that in Example 1, the 1d compressive strength and the 28 compressive strength are lower than those in Example 1. Moreover, for early-strength grouting materials, the higher the 3h compressive strength, the better. The strength difference between the grouting material and the base material needs to be considered. If the strength difference is too large, it is easy to generate tensile stress on the base material, and even cause spalling or secondary damage.
[0112] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A composite semi-flexible pavement early strength grouting material, characterized in that: The raw materials include the following parts by weight: 25-55 parts of cement, 10-30 parts of quartz sand, 9-15 parts of fly ash beads, 8-20 parts of microsilica powder, 2-8 parts of expansion agent, 0.16-0.3 parts of composite early strength water reducing agent, 0.05-0.2 parts of retarder and 25-45 parts of water; The composite early strength water reducing agent is compounded by an inorganic early strength agent, an organic early strength agent and a water reducing agent; The cement is composed of silicate cement and sulphoaluminate cement in a mass ratio of (10-20):(80-90).
2. The composite semi-flexible pavement early strength grouting material according to claim 1, characterized in that: The mass ratio of the inorganic early strength agent to the organic early strength agent is (0.1-0.3):(0.12-0.55); the total mass concentration of the inorganic early strength agent and the organic early strength agent in the composite early strength water reducing agent is 25%.
3. The composite semi-flexible pavement early strength grouting material according to claim 1 or 2, characterized in that: The inorganic early strength agent includes one or more of calcium nitrate, sodium sulfate and potassium sulfate.
4. The composite semi-flexible pavement early strength grouting material according to claim 1 or 2, characterized in that: The organic early strength agent includes one or more of triethanolamine, diethanolamine, calcium formate and calcium acetate.
5. The composite semi-flexible pavement early strength grouting material according to claim 1 or 2, characterized in that: The water reducer includes one of a polycarboxylate water reducer, a naphthalene water reducer, an aminosulfonate, and an aliphatic water reducer.
6. The composite semi-flexible pavement early strength grouting material according to claim 1, characterized in that: The particle size of the quartz sand is 40-200 mesh; The content of silicon oxide in the fly ash floating beads is ≥50%, the average diameter is 0.16-1.41 μm, and the minimum particle size is 0.09 μm; The silicon dioxide content in the microsilica powder is ≥95%, the average diameter is 0.1-0.15 μm, and the minimum particle size is 0.01 μm.
7. The composite semi-flexible pavement early strength grouting material according to claim 1, characterized in that: The expansion agent includes one or more of sulphoaluminate expansion agents, calcium oxide expansion agents, and magnesium oxide expansion agents; The retarder includes one or more of citric acid, tartaric acid, sodium gluconate, boric acid and white sugar.
8. The method for preparing the composite semi-flexible pavement early strength grouting material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Cement, quartz sand, fly ash beads, microsilica powder and expansion agent are mixed uniformly to obtain mixture A; (2) Compounding an inorganic early strength agent, an organic early strength agent and a water reducer to obtain a composite early strength water reducer, and premixing the obtained composite early strength water reducer with a retarder and water to obtain a liquid phase B; (3) adding the liquid phase B obtained in step (2) to the mixture A obtained in step (1) in portions, and obtaining the composite semi-flexible pavement early strength grouting material through forced mixing and stirring; There is no order of precedence for steps (1) and (2).
9. Use of the composite semi-flexible pavement early strength grouting material according to any one of claims 1 to 7 in road engineering.
Citation Information
Patent Citations
High-early-strength cement-based filling material for semi-flexible composite pavements
CN105016678A
Cement grouting material as well as preparation method and application thereof
CN113045278A
Cement-based grouting material for semi-flexible pavement and preparation method of cement-based grouting material
CN113277809A
High-flow-state early-strength semi-flexible pavement grouting material and preparation method thereof
CN115947578A
Self-compacting high-toughness semi-flexible pavement grouting material and preparation method thereof
CN116514483A
Cited By
High-strength and high-ductility composite concrete for roadbed reinforcement and preparation method thereof
CN121651800A